PERANAN GURU PENDIDIKAN AGAMA ISLAM DALAM MEMOTIVASI ANAK DIDIK - Zulhimma, Zulhimma (Darul Ilmi: Jurnal Ilmu Kependidikan dan Keislaman, 2014)
AbstractTo be a teacher is a holy duty because to educate yungsters means a teahcer plays as the pioner interacting directly with the students, that is why a teacher functions to decide the future.Keywords: Tachers’role, Islam, Motivation and Students